The Association of Post-traumatic and Postmigration Stress with Pain and Other Somatic Symptoms: An Explorative Analysis in Traumatized Refugees and Asylum Seekers. Issue 1 (6th March 2017) - Morina, Naser; Kuenburg, Alexa; Schnyder, Ulrich; Bryant, Richard A; Nickerson, Angela; Schick, Matthis
Abstract: Objective: Post-traumatic stress disorder (PTSD) and somatic symptoms, such as pain, are frequently seen in refugees. Their relationship is poorly understood, and the treatment of these comorbid conditions can be very challenging. The current cross-sectional study examined pain and other somatic symptoms and their relationship with trauma history, PTSD symptom clusters, and current living difficulties among treatment-seeking refugees. Methods: One hundred thirty-four treatment-seeking traumatized refugees (78% male, mean age = 42 years) were assessed regarding lifetime traumatic experiences, symptoms of post-traumatic stress, overall pain and somatic symptoms, and postmigration living difficulties. Results: An exploratory factor analysis of the 12 somatic symptoms revealed two distinct factors: somatic symptoms related to bodily dysfunction ("weakness") and somatic symptoms related to increased sympathetic activity ("arousal"). DSM-5 PTSD Criteria D "alterations in cognitions and mood" and E "alterations in arousal and reactivity" were primarily related to "weakness, " while PTSD Criterion E "alterations in arousal and reactivity" and postmigration living difficulties were associated with "arousal." Overall pain was associated primarily with living difficulties and PTSD Criterion D and Criterion E. Conclusions: Results indicate that somatic symptoms are of considerable concern among traumatized refugees and that different patterns of somatic symptoms are associated with different clusters of PTSD symptoms. The findings contribute to the better understanding of the symptom presentation of traumatized people who are experiencing somatization and potentially inform treatment directions and highlight the importance of screening for PTSD in refugees presenting with pain and somatic symptoms.